(untitled) (Revista Latino-Americana de Enfermagem, 2006)
Usually colleges are evaluated by the quality of the knowledge and technical training offered to the students. Little attention is given to the acquisition of the values, behaviors and attitudes necessary to assume their professional role. This exploratory study aims to increase understanding of the professional socialization process that occurs at nursing schools and the results obtained through the socialization of professional values and standards. The educational experience of nursing students involves more than a body of scientific knowledge and the acquisition of abilities to provide care to patients. Questionnaires were filled out by 278 students of two public Nursing Schools in São Paulo state, 164 in school A and 114 in school B. The results indicated that some professional values, norms and behaviors are influenced by College years, studying at a College of Nursing during four years leads to a difference in values, norms and professional behavior.